UNDERSTANDING THE CUSTOMER CENTRIC APPROACH TO ADD VALUE TO SOCIAL ECRM (SECRM) - Arshi Naim (American Journals Publishing, 2022)
Social media is fastest and strongest growing platform and can be seen as a New Business Model (NBM) for firms to develop and conduct their business operations. This development has strengthened the social consumers and has motivated the firms to apply new technologies to align with the NBM. The most important Information Systems strategy for many firms is to make consumer as focal point for all business operations in Social Electronic Customer Relationship Management (SECRM). This is a new concept started only in 2009 as an e-business strategy for firms to enable customer relationship management (with social customers) utilizing social technology and termed as Social Electronic Customer Relationship Management (SECRM). There the many applications that are labeled as SECRM but all these applications lack the framework of working and do not have effective planning and design for the implementation in such a ways that customer relationship can be developed. It is also found that many firms are using SECRM just as one of the method of communication channel, selling platform but not many firms considering the SECRM as one of the strategy to build firm image and earn profit and eventually build good ECRM. This study tries to build a conceptual framework for plan and design for SECRM and explains the benefits of using customer centric approach to build SECRM. Results are based on secondary data collected from various web sources presenting the advantages of using customer centric approach to build SECRM and to for developing the conceptual framework for the plan.
Keywords: New Business Model; Social Electronic; Customer Relationship Management